2021
DOI: 10.1016/j.ultrasmedbio.2020.11.012
|View full text |Cite|
|
Sign up to set email alerts
|

Bulk Wave Velocities in Cortical Bone Reflect Porosity and Compression Strength

Abstract: The goal of this study is to evaluate whether ultrasonic velocities in cortical bone can be considered as a proxy for mechanical quality of cortical bone tissue reflected by porosity and compression strength. Micro-computed tomography, compression mechanical testing, and resonant ultrasound spectroscopy were used to assess, respectively porosity, strength, and velocity of bulk waves of both shear and longitudinal polarisations propagating along

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…These findings are supported by those of other authors who also observed an inverse correlation between porosity and compressive strength of β-TCP implants [29][30][31][32]. Peralta et al [33] specifically addressed this correlation in human bone: a 5% increase in porosity corresponded to a 20 MPa decrease in compressive strength, which is approximately 10% of the maximum compressive strength of human cortical bone samples. As mentioned above, the hybrid structure has a comparatively high compressive strength for its high porosity of 74.4%; accordingly, with the specific design of the column structure with macroporous filling based on the structure of human bone, the production of a predominantly microporous TCP scaffold with great mechanical resilience was successful.…”
Section: Porositysupporting
confidence: 75%
See 1 more Smart Citation
“…These findings are supported by those of other authors who also observed an inverse correlation between porosity and compressive strength of β-TCP implants [29][30][31][32]. Peralta et al [33] specifically addressed this correlation in human bone: a 5% increase in porosity corresponded to a 20 MPa decrease in compressive strength, which is approximately 10% of the maximum compressive strength of human cortical bone samples. As mentioned above, the hybrid structure has a comparatively high compressive strength for its high porosity of 74.4%; accordingly, with the specific design of the column structure with macroporous filling based on the structure of human bone, the production of a predominantly microporous TCP scaffold with great mechanical resilience was successful.…”
Section: Porositysupporting
confidence: 75%
“…At a temperature of 38.5°C, the compressive strength of compact bone decreases from 82.7 ± 11.3 MPa, measured in the direction of the Haversian canals, to 67.6 ± 10.9 MPa orthogonally [36]. Data on the compressive strength of human compact bone varies between values of 130 and 180 MPa [33,37]. As a result, the measured compressive strength values of all β-TCP implants tested in the present study were found to be well below the reference value for the compressive strength of human cortical bone.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…( 40,51 ) The method considers variations of porosity as a major source of variations of cortical bone elasticity, sound velocity, and fracture toughness in postmenopausal women. ( 52–54 ) Results of a first validation study in postmenopausal women confirmed a comparable fracture discrimination performance of the BDAT variables as aBMD for both vertebral and peripheral fractures. ( 41 ) However, axial transmission measurements do not provide direct image guidance and are restricted to patients with low BMI.…”
Section: Discussionmentioning
confidence: 70%
“…For example, Adami et al (50) technology by means of multimode waveguide dispersion analysis (40,51) . The method considers variations of porosity as a major source of variations of cortical bone elasticity, sound velocity and fracture toughness in postmenopausal women (52)(53)(54) . Results of a first validation study in postmenopausal women confirmed a comparable fracture discrimination performance of the BDAT variables as aBMD for both vertebral and peripheral fractures (41) .…”
Section: Discrimination Performancementioning
confidence: 99%
“…For example, Adami et al 44 35,45 . The method considers variations of porosity as a major source of variations of cortical bone elasticity, sound velocity and fracture toughness in postmenopausal women [46][47][48] . Results of a first validation study in postmenopausal women confirmed a comparable fracture discrimination performance of the BDAT variables as aBMD for both vertebral and peripheral fractures 41 .…”
Section: Discrimination Performancementioning
confidence: 99%